Examining the consumer attitudes of Generation Z in dark tourism based on involuntary eye movement - Mészáros, Boglárka Ágnes; Németh, Péter; Csapó, János (Vezetéstudomány / Budapest Management Review, 2025)
The present study explores the perceptions of Generation Z towards dark tourism by employing the prevalent eye-tracking method in neuromarketing. The objective is to ascertain the specific elements of the Transylvanian Vajdahunyadi Castle’s dark tourism supply that capture the attention of Generation Z, discern the emotional associations linked with these dark elements, and investigate whether the presence of individuals in these attractions influences the emotional experience. The findings of the research underscore that most respondents associate negative emotions with the dark elements of the castle. Simultaneously, there is an observed heightened sensitivity in consumer perception to the visualization of dark object elements associated with human presence, characterized by statistically verified elevated levels of negative emotions and diminished levels of positive and neutral emotions. Based on the authors’ knowledge and available scientific databases, no similar study combining such topic and methodology is present in tourism literature, justifying this research as gap-filling.